Text Messaging and Disaster Preparedness Aids Engagement, Re-Engagement, Retention, and Communication Among Puerto Rican Participants in a Human Immunodeficiency Virus (HIV) Self-Testing Study After Hurricanes Irma and Maria. (8th April 2023) - Brown, William; Lopez Rios, Javier; Sheinfil, Alan; Frasca, Timothy; Cruz Torres, Catherine; Crespo, Raynier; Dolezal, Curtis; Giguere, Rebecca; Lentz, Cody; Balán, Iván C.; Rael, Christine Tagliaferri; Febo, Irma; et al.
ABSTRACT: Objective: Hurricanes can interrupt communication, exacerbate attrition, and disrupt participant engagement in research. We used text messaging and disaster preparedness protocols to re-establish communication, re-engage participants, and ensure retention in a human immunodeficiency virus (HIV) self-test study. Methods: Participants were given HIV home test kits to test themselves and/or their non-monogamous sexual partners before intercourse. A daily text message-based short message service computer-assisted self-interview (SMS-CASI) tool reminded them to report 3 variables: (1) anal sex without a condom, (2) knowledge of partners' testing history, and (3) proof of partners' testing history. A disaster preparedness protocol was put in place for hurricanes in Puerto Rico. We analyzed 6315 messages from participants (N = 12) active at the time of Hurricanes Irma and Maria. Disaster preparedness narratives were assessed. Results: All participants were able to communicate sexual behavior and HIV testing via SMS-CASI within 30 days following María. Some participants (n = 5, 42%) also communicated questions. Re-engagement within 30 days after the hurricane was 100% (second week/89%, third week/100%). Participant re-engagement ranged from 0–16 days (average = 6.4 days). Retention was 100%. Conclusions: Daily SMS-CASI and disaster preparedness protocols helped participant engagement and communication after 2 hurricanes. SMS-CASI responses indicated high participant re-engagement, retention, and well-being.